2004
DOI: 10.1080/02688690400005081
|View full text |Cite
|
Sign up to set email alerts
|

Neurolisteriosis causing hydrocephalus, trapped fourth ventricle, hindbrain herniation and syringomyelia

Abstract: Central nervous system infection by Listeria monocytogenes is relatively uncommon, but is known to be highly morbid and fatal. We describe a case of listeria meningoencephalitis, wherein the acute episode was followed by a hitherto unreported conglomeration of severe and progressive neurological sequelae, in the form of supratentorial hydrocephalus, aqueduct block, trapped fourth ventricle, hindbrain herniation and syringomyelia. Pertinent literature is reviewed and the pathogenesis of the observed sequelae is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…3). Although a reduced CSF reabsorption through the impaired Pacchioni’s granulations cannot be excluded, in our opinion the most probable etiopathogenesis of the victim’s hydrocephalus is a postinfective obstruction of the fourth ventricle outlets, a previously described condition (7,8). …”
Section: Discussionmentioning
confidence: 79%
“…3). Although a reduced CSF reabsorption through the impaired Pacchioni’s granulations cannot be excluded, in our opinion the most probable etiopathogenesis of the victim’s hydrocephalus is a postinfective obstruction of the fourth ventricle outlets, a previously described condition (7,8). …”
Section: Discussionmentioning
confidence: 79%
“…Another series has shown that hydrocephalus develops in only one of 35 patients with Listeria meningitis [5]. The time of appearance of the hydrocephalus has varied from a few weeks to over one year [3,9]. In our case, hydrocephalus was manifested during the first week (day 7).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to tuberculous meningitis [3], hydrocephalus caused by Listeria meningitis has been uncommon [3,7,9,10]. Large series have demonstrated that 19% of CT scans from Listeria meningitis patients show hydrocephalus and abscess without distinguishing between the two of them [7].…”
Section: Discussionmentioning
confidence: 99%
“…Listeria infections are frequently transmitted through food. Listeria infections are associated with sepsis, meningoencephalitis, and granulomas7, 8). When infection due to listeria occurs, it can be fatal; the mortality rate is up to 30%.…”
Section: Discussionmentioning
confidence: 99%